Betaine affects muscle lipid metabolism via regulating the fatty acid uptake and oxidation in finishing pig - Sisi Li; Haichao Wang; Xinxia Wang; Yizhen Wang; Jie Feng (Journal of Animal Science and Biotechnology, 2017)
Abstract Background Betaine affects fat metabolism in animals, but the specific mechanism is still not clear. The purpose of this study was to investigate possible mechanisms of betaine in altering lipid metabolism in muscle tissue in finishing pigs. Methods A total of 120 crossbred gilts (Landrace × Yorkshire × Duroc) with an average initial body weight of 70.1 kg were randomly allotted to three dietary treatments. The treatments included a corn–soybean meal basal diet supplemented with 0, 1250 or 2500 mg/kg betaine. The feeding experiment lasted 42 d. Results Betaine addition to the diet significantly increased the concentration of free fatty acids (FFA) in muscle (P < 0.05). Furthermore, the levels of serum cholesterol and high-density lipoprotein cholesterol were decreased (P < 0.05) and total cholesterol content was increased in muscle (P < 0.05) of betaine fed pigs. Experiments on genes involved in fatty acid transport showed that betaine increased expression of lipoprotein lipase(LPL), fatty acid translocase/cluster of differentiation (FAT/CD36), fatty acid binding protein (FABP3) and fatty acid transport protein (FATP1) (P < 0.05). The abundance of fatty acid transport protein and fatty acid binding protein were also increased by betaine (P < 0.05). As for the key factors involved in fatty acid oxidation, although betaine supplementation didn’t affect the level of carnitine and malonyl-CoA, betaine increased mRNA and protein abundance of carnitine palmitransferase-1(CPT1) and phosphorylated-AMPK (P < 0.05). Conclusions The results suggested that betaine may promoted muscle fatty acid uptake via up-regulating the genes related to fatty acid transporter including FAT/CD36, FATP1 and FABP3. On the other hand, betaine activated AMPK and up-regulated genes related to fatty acid oxidation including PPARα and CPT1. The underlying mechanism regulating fatty acid metabolism in pigs supplemented with betaine is associated with the up-regulation of genes involved in fatty acid transport and fatty acid oxidation.